Developing nitrogen fertiliser management strategies for canola (Brassica napus L.) under conservation agriculture practices in the Western Cape - Du Toit, Etienne (Stellenbosch : Stellenbosch University, 2018)
Thesis (MA)--Stellenbosch University, 2018.